Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Jade Almeida - Almeida, Jade (2018)
Originaire de Guadeloupe, Jade Almeida intervient tous les jeudis sur la web radio Neoquebec et participe à divers projets mettant les femmes noires au centre de la narration. Elle se positionne contre la négrophobie et la misogynie noire et tente de naviguer l’institution académique dans une optique de décolonisation.
Keywords: afrique; afro-féminisme; amériques; approches et analyses; canada; caraïbes; cours; discours dominant; europe; fem3100; france; féminismes noirs; identités LGBTQIA2+; misogynoir; premier cycle; québec; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques